Presentation of the new IUFRO Working Party 1.01.13 - Ecology and silviculture of chestnut - Clark, Stacy L. (2022)
IUFRO is a global, non-profit, non-governmental and non-discriminatory organization established in 1892 with headquarters in Vienna, Austria. It unites about 650 member organizations in more than 120 countries representing over 15,000 scientists. The newborn IUFRO Working Party on ecology and silviculture of chestnut (Castanea) includes a team of researchers with expertise in forest management, ecology, and silviculture. The prerogative of the group is to INCLUDE researchers actively interested in PROPOSING, PARTICIPATING and SHARING common research ideas and themes. Goals of this group are to provide knowledge and promote research and management activities that: (i) improve production and sustainability of Castanea forests to serve economic, social, and ecological needs; (ii) restore Castanea trees where they have been extirpated or largely reduced due to non-native pests or pathogens; (iii) improve resilience of Castanea to impacts from climate change; (iv) innovate in multifunctional management approaches of Castanea forests towards valuing of and payment for ecosystem services. Given the wide range of products and functions provided by the Castanea forests, the research group will strive to interact with other units within Division 1 and across other IUFRO-Divisions.